2019
DOI: 10.2147/cmar.s203656
|View full text |Cite
|
Sign up to set email alerts
|

<p>Connexin 32 downregulation is critical for chemoresistance in oxaliplatin-resistant HCC cells associated with EMT</p>

Abstract: Background: Oxaliplatin (OXA)-based chemotherapy is critical in the management of advanced hepatocellular carcinoma (HCC); however, acquired drug resistance has largely restricted its clinical efficacy. This study aims to explore the key mechanisms and regulatory factors determining chemosensitivity in HCC. Methods: We developed OXA-resistant (OR) HCC cells and used multiple methods, including real-time RT-PCR, Western blot, immunofluorescence, transwell invasion assay, wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…Accumulating evidence has shown that EMT plays a crucial role in HCC invasion and metastasis [4][5][6]; EMT is characterized by the loss of epithelial cell polarity and cellcell contacts by downregulation of E-cadherin expression and upregulation of the expression of mesenchymal markers such as Vimentin [8]. Our previous investigation revealed that a partial EMT process was often activated in HCC tissues [15,16], supporting the hypothesis that EMT is partially responsible for HCC progression through mediating cell migration, invasion, and metastasis. In the present study, overexpression of STRN enhanced the migration and invasion capacities of Huh7 cells and induced the EMT phenotype.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Accumulating evidence has shown that EMT plays a crucial role in HCC invasion and metastasis [4][5][6]; EMT is characterized by the loss of epithelial cell polarity and cellcell contacts by downregulation of E-cadherin expression and upregulation of the expression of mesenchymal markers such as Vimentin [8]. Our previous investigation revealed that a partial EMT process was often activated in HCC tissues [15,16], supporting the hypothesis that EMT is partially responsible for HCC progression through mediating cell migration, invasion, and metastasis. In the present study, overexpression of STRN enhanced the migration and invasion capacities of Huh7 cells and induced the EMT phenotype.…”
supporting
confidence: 69%
“…. IHC was carried out on 4 μm thick, formalin-fixed, paraffin-embedded sections according to the two-step protocol that we described previously [15,16]. Anti-STRN (1 : 50, Proteintech), anti-Ecadherin (1 : 50, Abcam), and anti-Vimentin (1 : 100, Abcam) primary antibodies were used for immunohistochemical analysis.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
See 1 more Smart Citation
“…CCN2 regulates cell proliferation, chemotaxis, and migration, while ID-1 is involved in blocking cell differentiation [162,163,164]. The Cx32 tumor suppressor protein is associated with positive expression of E-cadherin and negative expression of vimentin [165,166]. Cx32 level is decreased in hepatocellular carcinoma resistant to oxaliplatin [165].…”
Section: Redox-mediated Mechanism Of Chemoresistancementioning
confidence: 99%
“…The Cx32 tumor suppressor protein is associated with positive expression of E-cadherin and negative expression of vimentin [165,166]. Cx32 level is decreased in hepatocellular carcinoma resistant to oxaliplatin [165]. Ataxin-2-line (ATXN2L) promotes migration and invasion and is elevated in oxaliplatin-resistant gastric cancer [167,168].…”
Section: Redox-mediated Mechanism Of Chemoresistancementioning
confidence: 99%